(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
In the era of modern digital transformation, ensuring information security has evolved from a mere technical task into a strategic priority that determines the stability of both nations and the private sector. This article analyzes current challenges in the field of information security, specifically focusing on the vulnerability of digital small and medium-sized enterprises (SMEs) to cyber threats. Beyond traditional technical solutions, the study explores the interplay between information security, the human factor, organizational culture, and governance processes. By synthesizing international best practices and recent scholarly research from the Scopus database (2012–2024), this study highlights the importance of implementing "maturity models" and "Responsible AI" (RAI) principles to enhance cyber resilience. Furthermore, practical and scientific recommendations are provided for enterprises with limited resources on adopting lightweight security frameworks. The research findings justify the necessity of building an information security system based on a holistic approach, harmonizing people, processes, and technologies.